Analisis Resepsi Orang Tua Di Bekasi Mengenai Kekerasan Dalam Film Girl In The Basement - Silitonga, Erikson Jermanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
Films are often a reflection of reality in real life. This research is an analysis of parents in Bekasi regarding the film Girl in the Basement to find out the meaning of parents to the film by using the Encoding-Decoding Theory. The film girl in the basement is a film that reflects the phenomenon of violence against children that occurs in the family scope. The methodology in this research is a qualitative approach, and the constructivist paradigm with the research method is reception analysis from Stuart Hall. This research also used a study to determine the position of the informant, which consists of dominant position, negotiation, and opposition. This study interviewed six informants, and this research concludes that the informants are obliged to say that the film Girl in the Basement is a crime genre film. Parents educate children about violence; and sexual abuse. In interpreting violence, four informants were in a dominant position (did not agree to vote), and the rest were negotiation and opposition.